1978
DOI: 10.1104/pp.61.4.654
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of [5-3H]Proline by Barley Leaves and Its Use in Measuring the Effects of Water Stress on Proline Oxidation

Abstract: The objective of these expenments was to determine the fate of tritium from the 5 position of proline aad to assess the vaidity of its loss to H20 as a measure of proline oxidation. When 15-3H1prollne was fed to barley (Horueum vulgare) (6). Second leaves were excised and allowed to wilt under a bank of incandescent lamps at a height adjusted to cause 25% of the original leaf weight to be lost in about I hr. Turgid leaves were kept with the cut end in water during this time. Radioactive compounds were added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 8 publications
1
31
2
Order By: Relevance
“…Pro catabolism is catalyzed by Pro dehydrogenase and P5C dehydrogenase (Hu et al, 1996;Peng et al, 1996). Suppression of Pro degradation has been demonstrated both in radiolabeling studies (Stewart and Boggess, 1978) and gene expression experiments (Kiyosue et al, 1996;Peng et al, 1996;Verbruggen et al, 1996). Recent studies have demonstrated that high Pro concentrations are present in the phloem sap of drought-stressed alfalfa (Girousse et al, 1996) and that the expression of a Pro-specific amino acid transporter is induced in response to water deficit and salt stress (Rentsch et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Pro catabolism is catalyzed by Pro dehydrogenase and P5C dehydrogenase (Hu et al, 1996;Peng et al, 1996). Suppression of Pro degradation has been demonstrated both in radiolabeling studies (Stewart and Boggess, 1978) and gene expression experiments (Kiyosue et al, 1996;Peng et al, 1996;Verbruggen et al, 1996). Recent studies have demonstrated that high Pro concentrations are present in the phloem sap of drought-stressed alfalfa (Girousse et al, 1996) and that the expression of a Pro-specific amino acid transporter is induced in response to water deficit and salt stress (Rentsch et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Proline (12) determination methods and salt (4) and wilting (12) treatments have also been described. Leaves were fed by placing their cut ends in a vial containing various compounds and kept in room light (about 11 jsmol m-2 s-' [4]).…”
Section: Methodsmentioning
confidence: 99%
“…In an earlier experiment on these populations (Thomas, 1990), the greater accumulation of proline in leaf blades (an average of 101 /imol g^^,, compared with 31 m easured here) was probably a consequence of the artificial drought technique, which involved adding frequent small volumes of water and resulted in a series of short droughts. If, as was inferred from the difficulty of measuring i^^., drought damaged the leaf membranes in treatment D8 (Thomas, 1986), then proline may have accumulated because compartmentation between production (in the cytoplasm or cbloroplasts) and oxidation (in the mitochondria) was disrupted, as proposed by Stewart & Bogges (1978).…”
Section: Adaptation To Droughtmentioning
confidence: 99%